“Capturing The Watchdog”: How Regional Budget Weaken The Role of Local Media? - Rianto, Puji; Maharani, Shinta; Gelgel, Ni Made Ras Amanda; Wahyudi, Risky; Afifi, Subhan (Mediator: Jurnal Komunikasi, 2023)
The political economy perspective suggests that the organization and financing of mass media influence media content. This research examines how the regional revenue and expenditure budget (APBD) financing has affected (the quality of) content and public communication. The study was conducted in Yogyakarta and Bali. This study uses qualitative methods. Data is collected through in-depth interviews and observations of the news. In-depth interviews were conducted with journalists, academics, and media analysts in Yogyakarta and Bali. This research found that the APBD significantly contributes as the revenue source of local media, particularly during the COVID-19 pandemic. Some media outlets even exhibit high dependency on APBD, as indicated by the sum of APBD they received. This has weakened the role of local media as a watchdog for local government while also creating a crisis for local public communication. Public communication today is predominantly filled with news emphasizing publicity rather than critical and investigative coverage of local issues. As a result, efforts to create an informed society as a prerequisite for democracy would be difficult to realize. The community’s involvement in local democracy is greatly defined by the quality of information they receive.